2008
DOI: 10.1007/s11547-008-0232-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of perfusion-weighted imaging at 3 Tesla in the assessment of malignancy of cerebral gliomas

Abstract: Three-Tesla PWI helps to distinguish necrosis from tumour mass, infiltrating tumour from oedema and high-grade from low-grade gliomas. It enhances the magnetic resonance (MR) assessment of cerebral gliomas and provides useful information for planning surgical and radiation treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 21 publications
1
12
0
1
Order By: Relevance
“…Previous studies have reported that both dynamic susceptibility contrast-PWI and arterial spin-labeling PWI can distinguish histologic grades of gliomas. 29,30 However, PWI had limited usefulness in the differentiation of subgroups of oligodendrogliomas with considerable overlap in rCBV max and maximal cerebral blood flow between low and high grades. 21,29,31 One study reported specific genotypic differences in oligodendrogliomas by use of dynamic susceptibility contrast-PWI, 11 with significantly higher rCBV max in only low-grade oligodendrogliomas with 1p/ 19q LOH.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that both dynamic susceptibility contrast-PWI and arterial spin-labeling PWI can distinguish histologic grades of gliomas. 29,30 However, PWI had limited usefulness in the differentiation of subgroups of oligodendrogliomas with considerable overlap in rCBV max and maximal cerebral blood flow between low and high grades. 21,29,31 One study reported specific genotypic differences in oligodendrogliomas by use of dynamic susceptibility contrast-PWI, 11 with significantly higher rCBV max in only low-grade oligodendrogliomas with 1p/ 19q LOH.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the lenticulostriate arteries were visualised by 7 T MR angiography in vivo, and the depiction of microvasculature as small as 100 µm was achieved by ultrahigh-field MR systems [5,18]. At 1.5 T and 3 T other important MR techniques for the evaluation of tissue vascularity like perfusion MRI and dynamic susceptibility contrast-enhanced MRI measure the increased cerebral blood flow and blood volume in tumour areas, but with limited morphological information compared with T2*-w images [19,20]. Neither technique is currently established for 7 T MRI.…”
Section: Discussionmentioning
confidence: 99%
“…For intracranial tumors, 3.0 T scanners have shown better SNR, spatial and temporal resolution, contrast-to-noise ratio, and spectral resolution than 1.5 T scanners with the same acquisition parameters [76][77][78][79] . However, the applications in other regions of the body, the added value of 3.0 T compared with 1.5 T scanners is still controversial, due to issues such as specific absorption rate and motion and susceptibility artifacts.…”
Section: Clinical and High-field-strength Mri Scannersmentioning
confidence: 99%